2019
DOI: 10.1080/10942912.2019.1614951
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and chemical compositions of Pingwu Fuzhuan brick-tea, a distinctive post-fermentation tea in Sichuan province of China

Abstract: Pingwu Fuzhuan brick tea (PWT), a distinctive post-fermentation tea originated from Pingwu region of Sichuan province in China, is a popular "western road" border-selling tea. In this study, we investigated characteristics and chemical compositions of PWT, together with comparing its physicochemical properties with other regions of Fuzhuan brick teas (FBTs). Firstly, inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the geographical origin of FBTs, and the profiles of mineral elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Similarly, Koch and co-workers demonstrated that EGC and EGCG were the two major catechins in several green and black tea samples from different cultivation areas, although they found that the primary catechin in both green and black tea investigated is not EGCG but EGC [14,15]. EGC and EGCG have also been reported to be the major catechins in the final Fuzhuan brick teas samples [16]. The level of EGC in NFT (1013 mg/100 g) was higher than that in LBT (817 mg/100 g), but lower than that in BGT (4020 mg/100 g) and TOT (2604 mg/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Koch and co-workers demonstrated that EGC and EGCG were the two major catechins in several green and black tea samples from different cultivation areas, although they found that the primary catechin in both green and black tea investigated is not EGCG but EGC [14,15]. EGC and EGCG have also been reported to be the major catechins in the final Fuzhuan brick teas samples [16]. The level of EGC in NFT (1013 mg/100 g) was higher than that in LBT (817 mg/100 g), but lower than that in BGT (4020 mg/100 g) and TOT (2604 mg/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…HFD, which causes an increase in visceral fat deposition, has been identified as a major risk factor for obesity (Hou et al, 2020;Li, et al, 2017;Zhao, et al, 2017). Due to the presence of several polyphenols such as C, EC, EGC, GCG, EGCG, and ECG (Li et al, 2019), the consumption of FT could prevent weight gain and metabolic disorders induced by HFD feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic yellow cleistothecia called “golden flowers” are traditionally judged as a quality standard of Fu‐zhuan tea (Li et al, 2019). Due to the difference in processing techniques, golden flowers were hardly found in solid‐state fermentation of pu‐erh tea.…”
Section: Introductionmentioning
confidence: 99%